Studi Morfometrik Paku Kawat (Lygodium) di Sumatera Barat - Revi Novila Shinta; Ardinis Arbain; - Syamsuardi (Universitas Andalas, 2012)
Morphometrics study of climbing ferns (Lygodium) in West Sumatra had been conducted from December 2011 to April 2012. This study used survey method and direct observation. The result of this study indicated that four species were identified: Lygodium microphyllum, L. flexuosum, L. longifolium dan L. circinnatum has found in The Biological Education and Research Forest (HPPB), Silokek and Harau. The fertile leaflets of L. microphyllum are deltoid and sterile leaflets are elongatus. The fertile and sterile leaflets of L. flexuosum are elongatus. The number of L. microphyllum leaflets range from 9-12 and L. flexuosum range from 10-13. The fertile leaflets of L. longifolium are palmati-partitus with 1-2 lobed and sterile leaflets are palmatus with 3-4 lobed, then the fertile leaflets of L. circinnatum are palmati-partitus with 2 or 4 lobed and sterile leaflets are palmatus with 4-5 lobed.All of the spesies coulb be classified in to 2 clusters, there were high morphological similarities among spesies in each cluster.Keywords: Lygodium, climbing fern, morphometrics, West Sumatra